Detecting location of construction defects in drilled shafts using frequency tomography analysis of cross-hole sonic logging - Abi Shdid, Caesar (2014)
Cross-hole Sonic Logging (CSL) is the standard method used in evaluating the integrity of deep foundations for bridges, such as drilled shafts, and is based on travelling ultrasonic waves between probes in parallel tubes. Several studies have used arrival time and wave speed, such as in cross-hole tomography, to detect construction defects in drilled shaft foundations. A processing method for three-component wide-band CSL data is presented—named Frequency Tomography Analysis (FTA). It uses changes in color of the frequency amplitude of the received signal in the location of defects. The method transfers time-domain data to frequency-domain data of the signals propagated between the tubes using Fast Fourier Transform (FFT). The method is performed after a CSL test has determined the high probability of an anomaly in a given area. The procedure improves the location accuracy and further characterizes the features of the defect. The new technique is validated experimentally using two drilled shaft samples constructed with foam pieces inserted throughout the length of the shaft inside the rebar cage before concrete placement, to replicate construction defects. FTA is then utilized after the CSL tests to detect the location of the defects. The technique proves to have a very high resolution and can determine the exact location of any void or defect inside the rebar cage of a drilled shaft. This provides a significant improvement to current techniques used in quality control during construction of bridges.